Abordagem Kaplan: sistematização de uma metodologia de ensino de piano - Oliveira Filho, Manoel Theophilo Gaspar de (2020)
This research aimed to systematize the piano teaching methodology of the Argentine-Brazilian professor José Alberto Kaplan, who worked in Paraíba as well as at UFPB between 1964 and 1996. In order to better understand the methodological procedures adopted by this professor, we interviewed former students and people close to him, mentioned in his autobiography (KAPLAN, 1999). When comparing the content of the interviews with the reading of Kaplan's pedagogical work (1966; 1977; 1987; 1999), we realize that the Kaplan Approach proposes a modern and interdisciplinary view of piano teaching, supported by a solid theoretical basis which is reinforced by the musical experience of professor Kaplan. Taking Luca Chiantore's (2001) Historia de la técnica pianística as a reference, we have analyzed the Kaplan Approach in dialogue with some of the main works of piano pedagogy of the last three centuries. In addition to this historical panorama, we have compared the Kaplan Approach to the pedagogical practice of four other piano teachers whose methodologies were also subject of research: Ludwig Deppe (CALAND, 1903), Sumiko Mikimoto (HOSAKA, 2009), Pietro Maranca (CABEZAS, 2006) and Dorothy Taubman (MILANOVIC, 2011), in addition to also analyzing the intersections between the Kaplan Approach and the Alexander Technique (2010; ALCANTARA, 2013). The results suggest that the Kaplan Approach, for its scientific basis, for its pioneering spirit at the regional, national and international levels, and for the prominence it gives to the sense of proprioception and the body as a source of knowledge, deserves greater dissemination and prominence within the scope of piano pedagogy.